PENGEMBANGAN PROSEDUR PERHITUNGAN KEKUATAN STRUKTUR BETON BANGUNAN GEDUNG SEDERHANA MENURUT SNI 2847:2019 - Sania Bilqisty Aulia Rahman (Universitas Pendidikan Indonesia (UPI), 2022)
This study intends to develop and test the feasibility of learning media for the procedure for calculating the strength of a simple building structure according to SNI 2847:2019 in the Construction Business Planning subject at the State Vocational High School 3 Yogyakarta with a suitable achievement target for use. The research method used is RD with a 4D development model. Data collection techniques: observation and instruments. Observations were made to identify problems, determine drafts and learning indicators presented in the media. The instrument was carried out to obtain feasibility validation from material experts, media experts, and teachers of construction and property business planning subjects. The data analysis technique used qualitative descriptive analysis. The results are in the form of a procedure module for calculating the strength of a simple building structure according to SNI 2847:2019 with a material scope: load calculation, the strength of the slab and beam structure with reinforced concrete material. The results of validation by material experts, media experts, and teachers stated that the media was in the